2018
DOI: 10.3390/mi9020049
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Mechanics in Brittle–Ductile Cutting Mode Transition

Abstract: This paper presents an investigation of the mechanism of the brittle–ductile cutting mode transition from the perspective of the mechanics. A mechanistic model is proposed to analyze the relationship between undeformed chip thickness, deformation, and stress levels in the elastic stage of the periodic chip formation process, regarding whether brittle or ductile mode deformation is to follow the elastic stage. It is revealed that, the distance of tool advancement required to induce the same level of compressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…It was believed that with the increase of cutting depth, 6H-SiC experienced the transition from elastic deformation to plastic deformation and then to intermittent cleavage (Wu et al, 2017). Xiao et al studied the relationship between cutting thickness and stress through MD simulation and concluded that when the cutting depth became small enough, the tensile stress would become lower than the critical tensile stress of brittle fracture, which was not enough to cause brittle fracture (Xiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that with the increase of cutting depth, 6H-SiC experienced the transition from elastic deformation to plastic deformation and then to intermittent cleavage (Wu et al, 2017). Xiao et al studied the relationship between cutting thickness and stress through MD simulation and concluded that when the cutting depth became small enough, the tensile stress would become lower than the critical tensile stress of brittle fracture, which was not enough to cause brittle fracture (Xiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These benefits are especially noticeable with, for example ceramics, polycrystalline cubic boron nitride (PcBN) and tungsten carbide tools which are commercially available as super-hard tool materials. Different approaches, entailing experimental [1,3,4,5,6,7,9,10,11,12,13], analytical [14,15], and FEM [16,17,18,19,20,21,22,23,24,25,26,27,28,29], have been utilized to examine the performance of a wide range of machining operations in terms of surface quality, generated cutting force and tool wear. Nevertheless, the potential of the precision hard turning process has not been fully realized as of yet.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there can be substantial differences between the physical principles that govern the underlying phenomenon of this technique at the macro scale. Resulting in undesirable changes to the chip formation and surface generation processes [10,11]. In particular, in contrast to conventional turning where the obtainable surface roughness decreases proportionally with the reduction of undeformed chip thickness (applied feed), in precision hard turning the undeformed chip thickness can be smaller than the cutting edge radius of the tool [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors influencing the brittle-ductile transition depth. Blake et al and Nakasuji et al [22,23] found that, for germanium and silicon, the tool rake angle and clearance angle had great effects on the brittle-ductile transition depth but cutting speed showed negligible effect. Meanwhile, the brittle-ductile transition depth was influenced slightly by nose radius for germanium while it was sensitive to the nose radius for silicon.…”
Section: Introductionmentioning
confidence: 99%